2016
DOI: 10.1111/clr.12915
|View full text |Cite
|
Sign up to set email alerts
|

A wide mesio‐distal gap in sites of congenitally missing maxillary lateral incisors is related to a thin alveolar ridge

Abstract: In patients congenitally missing I2, an increased mesio-distal gap width correlates significantly with reduced edentulous AR dimensions. A mesio-distal gap of >6 mm was associated with thin bucco-palatal alveolar ridges, precluding straightforward implant placement in 60-80% of the cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…On the other hand, a geometric morphometric evaluation of the whole mandibular cross‐section in the current group of patients (Bertl, Bertl et al., ) revealed that cross‐sectional mandibular size and shape differed significantly between patients with and without P2 agenesis, and that the differences extended beyond a localized morphological change at the agenesis sites, and involved the neighboring teeth and body of the mandible. Nevertheless, the average mesio‐distal crown dimension of the primary second molar is about 10 mm (Harris & Lease, ); the fact that in the present material in the AWO group straightforward placement of an implant, which was about 1 mm larger in Ø comparing to what was simulated in the above‐mentioned study (Bertl, Grotthoff et al., ), was possible in 50% of the cases and may indicate that the dimensions of the alveolar bone in the posterior aspects of the jaws are relatively less influenced by agenesis comparing to the anterior aspects. However, the observed differences regarding the possibility for straightforward implant placement in anterior and posterior jaw aspects, as observed in the two studies, may simply be due to differences in the average bucco‐oral dimensions of the anterior and posterior jaw aspects (i.e., thinner vs. thicker, respectively); in other words, despite similar relative influence by agenesis in anterior and posterior jaw aspects, the remaining bucco‐oral width of the alveolar ridge in the posterior aspects of the jaw was enough for straightforward implant placement.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…On the other hand, a geometric morphometric evaluation of the whole mandibular cross‐section in the current group of patients (Bertl, Bertl et al., ) revealed that cross‐sectional mandibular size and shape differed significantly between patients with and without P2 agenesis, and that the differences extended beyond a localized morphological change at the agenesis sites, and involved the neighboring teeth and body of the mandible. Nevertheless, the average mesio‐distal crown dimension of the primary second molar is about 10 mm (Harris & Lease, ); the fact that in the present material in the AWO group straightforward placement of an implant, which was about 1 mm larger in Ø comparing to what was simulated in the above‐mentioned study (Bertl, Grotthoff et al., ), was possible in 50% of the cases and may indicate that the dimensions of the alveolar bone in the posterior aspects of the jaws are relatively less influenced by agenesis comparing to the anterior aspects. However, the observed differences regarding the possibility for straightforward implant placement in anterior and posterior jaw aspects, as observed in the two studies, may simply be due to differences in the average bucco‐oral dimensions of the anterior and posterior jaw aspects (i.e., thinner vs. thicker, respectively); in other words, despite similar relative influence by agenesis in anterior and posterior jaw aspects, the remaining bucco‐oral width of the alveolar ridge in the posterior aspects of the jaw was enough for straightforward implant placement.…”
Section: Discussionmentioning
confidence: 54%
“…On the other hand, a geometric morphometric evaluation of the whole mandibular cross-section in the current group of patients revealed that cross-sectional mandibular size and shape differed significantly between patients with and without P2 agenesis, and that the differences extended beyond a localized morphological change at the agenesis sites, and involved the neighboring teeth and body of the mandible. Nevertheless, the average mesio-distal crown dimension of the primary second molar is about 10 mm (Harris & Lease, 2005); the fact that in the present material in the AWO group straightforward placement of an implant, which was about 1 mm larger in Ø comparing to what was simulated in the above-mentioned study (Bertl, Grotthoff et al, 2016), conflict of interest, and no external funding was obtained for performing the present study.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations